Students’ Intuition of Field Independent and Field Dependent in Solving Divergence Mathematical Problem - Abidin, Zainal; Jarmita, Nida (Kreano, Jurnal Matematika Kreatif-Inovatif, 2020)
In solving divergent mathematical problem, there is a different mental activity of formal cognitition. The activity is wel known as intuitive cognition or intuition. This study aims at exploring students’ intuition styles of Field Independent and Field Dependent when they solve divergent mathematical problems. The subjects of this study were GEEFT-test-selected students of MAN Model Banda Aceh who had intuition styles of Field Independent and Field Dependent. The findings of this study showed that field independent students used direct affirmatory intuition in understanding problems, direct and global anticipatory intuition in making plans for solutions, and global anticipatory intuition in solving divergent mathematical problems. On the other hand, field dependent students used direct affirmatory intuition in understanding problems, direct and global anticipatory intuition in making problem-solving plans, and anticipatory global intuition in re-examining divergent mathematical problem solving.Penelitian ini bertujuan untuk mengeksplorasi intuisi siswa yang bergaya kognitif Field Independent dan Field Dependent saat memecahkan masalah matematika divergen. Dalam penelitian ini subjeknya adalah siswa MAN Model Banda Aceh yang memiliki gaya kognitif field independent dan field dependent, dipilih menggunakan tes GEEFT. Temuan dalam penelitian ini diperoleh bahwa siswa field independent menggunakan intuisi afirmatori yang bersifat langsung dalam memahami masalah, dalam membuat rencan pemecahan menggunakan intuisi antisipatori bersifat langsung dan global, dan dalam memecahkan masalah matematika divergen menggunakan intuisi antisipatori yang bersifat global. Sedangkan siswa field dependent menggunakan intuisi afirmatori yang bersifat langsung dalam memahami masalah, dalam membuat rencana pemecahan masalah menggunakan intuisi antisipatori yang besifat langsung dan global, dan dalam memeriksa kembali pemecahan masalah matematika divergen menggunakan intuisi antisipatori yang bersifat global.